2008
DOI: 10.1128/iai.00532-08
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Vibrio cholerae Outer Membrane Vesicles Induces Protective Immunity in Mice

Abstract: The gram-negative bacterium Vibrio cholerae releases outer membrane vesicles (OMVs) during growth. In this study, we immunized female mice by the intranasal, intragastric, or intraperitoneal route with purified OMVs derived from V. cholerae. Independent of the route of immunization, mice induced specific, high-titer immune responses of similar levels against a variety of antigens present in the OMVs. After the last immunization, the half-maximum total immunoglobulin titer was stable over a 3-month period, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
211
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(226 citation statements)
references
References 101 publications
9
211
2
4
Order By: Relevance
“…4). Immunogenic proteins of size between 35 to 45 kDa were reportedly seen in OMV of Vibrio cholera (Schild et al, 2008). Silver staining identified LPS in outer membrane vesicles of B. abortus which revealed both heavy and light silver-stained bands occurring within a repeating unit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Immunogenic proteins of size between 35 to 45 kDa were reportedly seen in OMV of Vibrio cholera (Schild et al, 2008). Silver staining identified LPS in outer membrane vesicles of B. abortus which revealed both heavy and light silver-stained bands occurring within a repeating unit.…”
Section: Resultsmentioning
confidence: 99%
“…Discovered 40 years ago, the only licensed vaccine is Neisseiria meningitis vaccine used successfully in humans (Kimura et al, 2011). Vibrio cholera and Bordetella pertusis OMV elicit protection in mice model (Schild et al, 2008). OMV can be a vaccine candidate due to heterogeneous composition and diverse functions.…”
Section: Introductionmentioning
confidence: 99%
“…We successfully applied this strategy to isolate OMVs from a LPS acyltransferase mutant strain, demonstrating that reduction of OMV endotoxicity can be achieved without diminishing the immunogenic potential by genetic modification resulting in underacylated lipid A [10]. Overall, we demonstrated the induction of a specific, long-lasting, high-titer, protective immune response upon mucosal immunization of mice with V. cholerae OMVs [7,8]. Interestingly, throughout our studies protection against O1 and O139, representing the two clinically relevant serogroups of V. cholerae, was only achieved by immunization with a mixture of O1 and O139 OMVs.…”
mentioning
confidence: 90%
“…Thus, OMVs are likely a key factor in effecting an inflammatory response to pathogens, being immunogenic and capable of eliciting proinflammatory responses. Immunization with Vibrio cholera OMVs induces protection in mice (Schild, 2008); the OMVs immunized mice were protected against Salmonella infections (Alaniz, 2007). Furthermore, OMVs influence inflammation and disease in vivo; it was shown that, in response to Helicobacter pylori and Pseudomonas aeruginosa OMVs (Bauman, 2006), epithelial cells produce interleukin-8, a cytokine that plays a fundamental role in neutrophil and monocyte recruitment.…”
Section: Outer Membrane Blebbingmentioning
confidence: 99%